Quantifying On‐Farm Nitrous Oxide Emission Reductions in Food Supply Chains. Issue 10 (7th October 2020) - Eagle, A. J.; McLellan, E. L.; Brawner, E. M.; Chantigny, M. H.; Davidson, E. A.; Dickey, J. B.; Linquist, B. A.; Maaz, T. M.; Pelster, D. E.; Pittelkow, C. M.; van Kessel, C.; Vyn, T. J.; et al.
Abstract: Reducing nitrous oxide (N2 O) emissions from agriculture is critical to limiting future global warming. In response, a growing number of food retailers and manufacturers have committed to reducing N2 O emissions from their vast networks of farmer suppliers by providing technical assistance and financial incentives. A key challenge for such companies is demonstrating that their efforts are leading to meaningful progress toward their climate mitigation commitments. We show that a simplified version of soil surface nitrogen (N) balance—or partial N balance—the difference between N inputs to and outputs from a farm field (fertilizer N minus crop N), is a robust indicator of direct N2 O emissions from fields with maize and other major rainfed temperate‐region crops. Furthermore, we present a generalized environmental model that will allow food‐supply‐chain companies to translate aggregated and anonymized changes in average N balance across their supplying farms into aggregated changes in N2 O emissions. This research is an important first step, based on currently available science, in helping companies demonstrate the impact of their sustainability efforts. Plain Language Summary: As a powerful greenhouse gas, nitrous oxide that is emitted from agriculture contributes to climate change. Reductions in these emissions are not only possible—they are critical to addressing climate change. Food companies and others wanting to reduce nitrous oxide emissions in their food supply chains are looking for a way to show evidence of progress. Our research shows that a simple calculation of nitrogen (N) balance in crop fields (N in fertilizer minus N in the harvested crop) can be used as an indicator of nitrous oxide emissions. At the large scale, reducing high N balances will reduce overall emissions. We demonstrate the strong relationship between N balance and nitrous oxide emissions and show how this simple model can be used at scale to bring about positive environmental change. Key Points: Nitrogen balance is a robust indicator of nitrous oxide emissions from agricultural cropland Food‐supply‐chain companies and others can scale up field‐level N balance values to measure progress toward sustainability goals over time The relationship between N balance and N2 O emissions is nonlinear, so the greatest benefit will come from reducing high field‐scale N balances